Agency, democracy, and nature : the U.S. environmental movement from a critical theory perspective - Brulle, Robert J. (MIT Press, 2000)
Annotation In this book Robert Brulle draws on a broad range of empirical and theoretical research to investigate the effectiveness of U.S. environmental groups. Brulle shows how Critical Theory--in particular the work of Jürgen Habermas--can expand our understanding of the social causes of environmental degradation and the political actions necessary to deal with it. He then develops both a pragmatic and a moral argument for broad-based democratization of society as a prerequisite to the achievement of ecological sustainability. From the perspectives of frame analysis, resource mobilization, and historical sociology, using data on more than one hundred environmental groups, Brulle examines the core beliefs, structures, funding, and political practices of a wide variety of environmental organizations. He identifies the social processes that foster the development of a democratic environmental movement and those that hinder it. He concludes with suggestions for how environmental groups can make their organizational practices more democratic and politically effective.